2011
DOI: 10.1007/s00216-011-5458-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar organic compounds in fine particles: quantification by thermal desorption–GC/MS and evidence for their significant oxidation in ambient aerosols in Hong Kong

Abstract: Nonpolar organic compounds (NPOCs) in ambient particulate matter (PM) commonly include n-alkanes, branched alkanes, hopanes and steranes, and polycyclic aromatic hydrocarbons (PAHs). The recent development of thermal desorption-gas chromatography/mass spectrometry (TD-GC/MS) has greatly reduced time and labor in their quantification by eliminating the laborious solvent extraction and sample concentration steps in the traditional approach that relies on solvent extraction. The simplicity of the TD-GCMS methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
1
16
0
3
Order By: Relevance
“…This indicates that vehicle exhaust is likely a dominant source for hopanes at these sites. Yu et al [] found similar results of vehicle emissions dominating ambient hopane concentrations at sites nearby in Hong Kong. However, much of the data in this study are at higher hopane/EC ratios than the Zhujiang tunnel profile, which that either the vehicle emission contribution favors the gasoline profile more than the tunnel data or an additional source is influencing the ambient data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that vehicle exhaust is likely a dominant source for hopanes at these sites. Yu et al [] found similar results of vehicle emissions dominating ambient hopane concentrations at sites nearby in Hong Kong. However, much of the data in this study are at higher hopane/EC ratios than the Zhujiang tunnel profile, which that either the vehicle emission contribution favors the gasoline profile more than the tunnel data or an additional source is influencing the ambient data.…”
Section: Resultsmentioning
confidence: 99%
“…The primary component (i.e., directly emitted) of carbonaceous material collected at urban sites typically contributes about 30-60% to the total organics in the aerosol [Kuang et al, 2015;Zhao et al, 2009]. Among the primary components, nonpolar organic compounds (NPOCs) have been widely studied due to their use as source indicators and relative ease of analysis [Bi et al, 2003;Xu et al, 2013;Yadav et al, 2013;Yu et al, 2011;Zheng et al, 2000Zheng et al, , 2006. NPOCs aside, a number of polar organic compounds are also unique source tracers for PM 2.5 , such as levoglucosan, which is uniquely emitted by biomass-burning activities [Engling et al, 2006], and β-caryophyllinic acid, the tracer for the β-caryophyllene-derived secondary organic aerosol other polar organic tracers is more laborious and expensive, severely limiting their use in source apportionment studies.…”
Section: Introductionmentioning
confidence: 99%
“…There were several deviation points in the lower-left corner, and the values were smaller than the values of the tunnel and vehicle source profile, indicating mixed influence from traffic origins and degradation. Yu et al (2011) reported a more apparent linear distribution of data sets measured in Hong Kong and PRD, which can be attributed to their single vehicle source type.…”
Section: Degradation Of Organicsmentioning
confidence: 96%
“…Photochemical oxidation has great influences on the mass concentration and size-specific distribution of NPOCs, as well as on their removal and atmospheric fate (May et al, 2012). Photochemical decay could cause the ambient data to be distributed along a line emanating from the source profile in the ratio-ratio plot, with increasing photochemical age (Robinson et al, 2006;Yu et al 2011). EC shares common origins with PAHs and hopanes but they are subject to photodegradation.…”
Section: Degradation Of Organicsmentioning
confidence: 99%
“…At high concentrations, acute eczema of the skin and pulmonary edema may develop. Alkanes have also been found to penetrate rapidly into the fatty cells of the myelin sheath that surrounds nerve fibres, where they dissolve the cells and cause degeneration of the axons, interrupting the transference of impulses (Yu et al, 2011a). Alkenes are not found in crude petroleum but are present in some refined products, particularly in gasoline.…”
Section: Introductionmentioning
confidence: 98%